Why Does this Kid Keep Winking at Me? - Ashe, Laura R. (Optometry & Visual Performance, 2017)
Background: One of the more common types of congenital synkinetic abnormalities is Marcus Gunn Jaw Winking Syndrome. It is typically a unilateral condition in which the affected superior eyelid moves with mouth movement, and the identified ptosis improves upon opening the mouth. Case Report: A ten-week-old infant presented to The Eye Center at Southern College of Optometry due to the right superior lid moving simultaneously with mouth movement. The child had been seen at eight weeks of age for the same presentation at Le Bonheur Children's Hospital, where neurological testing was found to be normal. At TEC, she was diagnosed with Marcus Gunn Jaw Winking Syndrome. Possible sequelae of this condition include, but are not limited to, binocular vision and accommodative dysfunctions and potential amblyopia of the affected eye. Conclusion: This case presentation will serve to help other eye care professionals to recognize and to understand Marcus Gunn Jaw Winking Syndrome in the pediatric patient.